Effect of Speed Agility Quickness and Circuit Training on Lipid Profile of Soccer Players: An Observational Study - Sm Farooque; Mukesh Mitra; Prasanta Kumar Das (Physical Education Theory and Methodology, 2023)
Study purpose. This observational study aims to investigate the impact of a Speed Agility Quickness (SAQ) and Circuit training program on the lipid profile of soccer players. The study focuses on analyzing changes in high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very-low-density lipoprotein (VLDL) cholesterol concentrations after the intervention.